Finding Opportunity in a Crisis: The Analysis of Climate Change Representation on Teenager Activist’s Speeches - Mansyur, Siti Awaliyah; Gunawan, Wawan (Ranah: Jurnal Kajian Bahasa, 2025)
The study aims to reveal the ideology and representation of climate change in the speeches of youth activist Greta Thunberg using eco-critical discourse analysis from an ecolinguistic perspective. Data were collected from Thunberg's speeches and analysed through detailed discourse analysis techniques to uncover themes and ideological constructs. Results show that climate change is portrayed as a human-caused crisis requiring systemic and regulatory changes. The identified ideology, termed imaginative green radicalism, frames climate change as an opportunity for collective action rather than a burden. According to Stibbe's ecolinguistics’ criteria, this discourse qualifies as beneficial discourse and should be promoted widely in society. Abstrak Penelitian ini bertujuan untuk mengungkap ideologi dan representasi perubahan iklim dalam pidato aktivis remaja Greta Thunberg dengan menggunakan analisis wacana eko-kritis dari perspektif ekolingusitik. Data dikumpulkan dari pidato Thunberg dan dianalisis menggunakan teknik analisis wacana untuk mengidentifikasi tema dan konstruksi ideologi. Hasil menunjukkan bahwa perubahan iklim direpresentasikan sebagai krisis yang disebabkan oleh tindakan manusia yang memerlukan perubahan sistem dan regulasi. Ideologi yang ditemukan, disebut sebagai imaginative green radicalism, memandang perubahan iklim sebagai kesempatan untuk bekerja sama secara kolektif, bukan sebagai beban. Berdasarkan kriteria ekolingusitik Stibbe, wacana ini dikategorikan sebagai wacana menguntungkan (beneficial discourse) yang perlu dipromosikan secara luas di masyarakat.